2015
DOI: 10.1007/s10554-015-0699-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plaque characteristics on fractional flow reserve for coronary lesions with intermediate to obstructive stenosis: insights from integrated-backscatter intravascular ultrasound analysis

Abstract: The aim of this study was to determine the correlation between the fractional flow reserve (FFR) values and volumetric intravascular ultrasound (IVUS) parameters derived from classic gray-scale IVUS and integrated backscatter (IB)-IVUS, taking into account known confounding factors. Patients with unstable angina pectoris with the frequent development of vulnerable plaques often showed the discrepancy between the FFR value and the quantitative coronary angiography findings. Our target population was 107 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…In the present study, OCT-derived minimal lumen area and area stenosis are independent determinants for FFR, whereas morphometric plaque characteristics are not. These findings are consistent with previous intravascular ultrasound or OCT studies in which minimum lumen area or plaque area was associated with FFR [5,11,12], but the plaque composition such as necrotic core or dense calcium was not [5]. The finding that FFR and plaque characteristics are unrelated may result from an adaptive vascular response to aggravation of coronary atherosclerosis because positive vascular remodeling maintains the diameter of the lumen to some degree [13].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, OCT-derived minimal lumen area and area stenosis are independent determinants for FFR, whereas morphometric plaque characteristics are not. These findings are consistent with previous intravascular ultrasound or OCT studies in which minimum lumen area or plaque area was associated with FFR [5,11,12], but the plaque composition such as necrotic core or dense calcium was not [5]. The finding that FFR and plaque characteristics are unrelated may result from an adaptive vascular response to aggravation of coronary atherosclerosis because positive vascular remodeling maintains the diameter of the lumen to some degree [13].…”
Section: Discussionsupporting
confidence: 90%
“…The finding that FFR and plaque characteristics are unrelated may result from an adaptive vascular response to aggravation of coronary atherosclerosis because positive vascular remodeling maintains the diameter of the lumen to some degree [13]. However, a recent study showed that the volume of lipid plaque measured by integrated backscatter intravascular ultrasound was significantly associated with FFR [12]. In the present study, the angle or longitudinal length of lipid pool was correlated to FFR in the univariate analysis, but it was not in the multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Fractional flow reverse positive lesions had more lipids [13], presented higher PB and smaller MLA [14]. Furthermore, the length of the plaque and its volume positively correlated with FFR results as well [15].…”
Section: Discussionmentioning
confidence: 81%
“…Brown et al also reported no relationship between the invasive FFR value and the VH-IVUS derived plaque composition 21) . However, Sakurai et al reported that lipid plaque volume, evaluated using integrated backscatter IVUS, was significantly correlated with invasive FFR value 22) . Hüseyinova et al also reported that invasive FFR value negatively correlated with the necrotic core volume or presence of thin-cap fibroatheroma (TCFA) evaluated using VH-IVUS 23) .…”
Section: Discussionmentioning
confidence: 99%